Human extravillous trophoblasts bind but do not internalize antiphospholipid antibodies. (June 2016) - Viall, Chez A.; Chen, Qi; Stone, Peter R.; Chamley, Lawrence W.
Abstract: Introduction: Obstetric morbidity in women with antiphospholipid antibodies (aPLs) may reflect the adverse effects of aPLs on placental cells such as extravillous trophoblasts and the syncytiotrophoblast. Antiphospholipid antibodies may affect the syncytiotrophoblast after being internalised by members of the Low-density lipoprotein receptor (LDLR) family and the antigen of aPLs, β2 glycoprotein I. Aim: This study aimed to determine whether aPL internalization was a mechanism by which aPLs adversely affect extravillous trophoblasts. Method: of Study: Fluorescently-labelled monoclonal aPLs IIC5 or ID2 were incubated with first trimester extravillous trophoblast outgrowths and visualized by microscopy. The subcellular expression of β2 glycoprotein I and LDLR family members was investigated by live/permeabilised immunocytochemistry. Results: Unlike the syncytiotrophoblast of anchoring villi, monoclonal aPLs were not internalised by extravillous trophoblasts, which expressed LDLR family members intracellularly. The aPL IIC5 bound to the surface of extravillous trophoblasts in a pattern similar to the extracellular expression of β2 glycoprotein I. Conclusions: The mechanisms of action of aPLs are different in extravillous trophoblasts and the syncytiotrophoblast. The interaction of aPLs with the extravillous trophoblast surface, which may involve β2 glycoprotein I, is consistent with reports that aPLs trigger intracellular signaling cascades through cell-surface receptors. Highlights: Monoclonal antiphospholipid antibodies (aPLs) IIC5 and ID2 are lupus anticoagulants. The aPL IIC5 binds to, but is not internalised by, extravillous trophoblasts (EVTs). EVTs express some β2 glycoprotein I in an extracellular position. Intracellular expression of low-density lipoprotein receptor homologs may explain why EVTs don't internalise aPL.